2017
DOI: 10.1111/scs.12472
|View full text |Cite
|
Sign up to set email alerts
|

Meanings of troubled conscience and how to deal with it: expressions of Persian‐speaking enrolled nurses in Sweden

Abstract: The enrolled nurses understood themselves as caring people and not only caregivers. They knew that they should hear their conscience and respond to it by trying to be a caring person and acting according to their values. The findings should be interpreted in the given specific context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
0
9
0
1
Order By: Relevance
“…According to studies, conscience is an inner sense of right and wrong and acts as a guide to human behavior ( 8 , 12 ). The word conscience was derived from the Latin word "conscientia", rooting in the Greek word "synderesis".…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to studies, conscience is an inner sense of right and wrong and acts as a guide to human behavior ( 8 , 12 ). The word conscience was derived from the Latin word "conscientia", rooting in the Greek word "synderesis".…”
Section: Resultsmentioning
confidence: 99%
“…Ignoring conscience commands leads to conflict in nurses’ actions and behaviors, as Ford and Austin emphasized the importance of paying attention to conscience commands ( 10 ). Moreover, studies in nursing fields have shown that if the conflict of conscience is repeated in different care situations, nurses will suffer from a troubled conscience, accompanied by guilt, sadness, and helplessness ( 12 , 37 ) as the consequences of ignoring obedience to conscience. Moreover, studies showed that if nurses follow their conscience call, a sense of clear conscience is attained, obedience to conscience is exercised, and the conscience’s role is perceived positively ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this article, we have followed a common way to present this final interpretation. Like researchers in different contexts (41)(42)(43), we present the na€ ıve interpretation and the thematic structural analysis in this section and integrate the comprehensive understanding with the discussion of findings. In the presentation, we use the concept 'person' when describing participants' spiritual experiences in general.…”
Section: Resultsmentioning
confidence: 99%
“…Bu uyarı, onu görmezden gelene ya da durumla ilgilenene kadar devam eder [9]. Vicdanın sesine kulaklarını tıkama ya da karşılaşılan olumsuz durum için çözüm üretmede yetersiz kalma kişisel bütünlük için olduğu kadar fizyolojik, psikolojik, sosyal ve çalışma ortamı sağlığı için de bir tehdit kaynağıdır [8,10,11].…”
Section: Introductionunclassified